2008
DOI: 10.1038/nature07336
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity and intestinal microbiota in the development of Type 1 diabetes

Abstract: Type 1 diabetes (T1D) is a debilitating autoimmune disease that results from T cell-mediated destruction of insulin-producing β cells. Its incidence has increased during the past several decades in developed countries 1, 2, suggesting that changes in the environment (including human microbial environment) may influence disease pathogenesis. The incidence of spontaneous T1D in non-obese diabetic (NOD) mice can be affected by the microbial environment in the animal housing facility3 or by exposure to microbial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,418
5
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,754 publications
(1,483 citation statements)
references
References 39 publications
38
1,418
5
22
Order By: Relevance
“…Indeed, although Toll-like receptor (TLR) as well as Nod2 signaling had been implicated in modelling the intestinal ecosystem, 33 , 34 subsequent studies using littermate comparisons showed that these pathways did not exert the previously described effects on the gut microbiota composition. 20 , 35 Hence, these studies confirmed using littermates as the appropriate experimental setup when investigating host genetic effects in intestinal microbiota regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although Toll-like receptor (TLR) as well as Nod2 signaling had been implicated in modelling the intestinal ecosystem, 33 , 34 subsequent studies using littermate comparisons showed that these pathways did not exert the previously described effects on the gut microbiota composition. 20 , 35 Hence, these studies confirmed using littermates as the appropriate experimental setup when investigating host genetic effects in intestinal microbiota regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Reports have shown that children with type 1 diabetes have increased barrier defects in their small intestines ( [8] and reviewed in [35]) and have a higher incidence of enteroviral infections [36]. Moreover, recent studies have also implicated innate recognition of enteric commensal microbes in the modulation of diabetes suffered by NOD mice [37]. An altered commensal gut flora because of interrupted toll-like receptor (TLR) signalling was shown to prevent diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Innate and adaptive immune responses coordinated by epithelial TLR signalling modulate the enteric flora and in turn are affected by gut microbes [37,[39][40][41]. Epithelial TLR signalling is critical in maintaining intestinal epithelial integrity [40].…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of modern lifestyle diseases such as allergies, diabetes, inflammatory bowel diseases and obesity to epidemic levels strongly links changes in nutrition, gut microbiota and immune function. (Backhed et al, 2004;Ley et al, 2006;Noverr and Huffnagle, 2004;Vijay-Kumar et al, 2010;Wen et al, 2008).…”
Section: Microbiota: a Key Component Of Nutritional Immunologymentioning
confidence: 99%